The Use of Comic Natural Disaster Mitigation in Social Studies Learning to Improve Student Preparedness - Shabirah Sulistiyani; Supriatna, Nana; Wildan Insan Fauzi (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2022)
This research stems from the urgency of implementing mitigation education in schools, especially in areas with a high level of vulnerability to disasters. Basically, in Indonesia, the disaster mitigation curriculum is implemented by being integrated into subjects, including social studies. Based on its geographical location, SMPN 3 Cibadak, Sukabumi Regency, is an area crossed by the Cimandiri Fault, so it is vulnerable to earthquake disasters. In addition, the area is prone to disasters and ranks third nationally. This research was conducted based on observations and interviews with research subjects. This study aims to improve students’ disaster preparedness by using comics with the theme of disaster mitigation designed by researchers. The method used is the Class Action Research (CAR) model by Kemmis and Mc. Taggart. The results showed that comics and learning improvement steps could increase students’ disaster preparedness. The increase in preparedness was concluded based on the results of observations and also tests carried out. The thing that influences it is a story that relates things close to students and interesting for them. So that students have an interest in studying comics, and students’ understanding increases. In addition, it is influenced by the concepts that exist in comics such as "if history" or bringing students into integrated historical material presented in subjects that also contribute to understanding the content of comics. Besides, appropriate learning methods are needed and not only reading comics activities but are directed to other activities such as discussions, questions and answers, games, simulations or role playing with comics as scenarios.